The Future of AI in Geriatrics: Enhancing Care, Extending Independence, and Addressing Workforce Shortages - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The global demographic shift toward an aging population presents a significant challenge and opportunity for modern healthcare. As the number of individuals ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics